Antioxidant sensing by spiropyrans: Substituent effects and NMR spectroscopic studies - Garcia, Joel E. (Animo Repository, 2019)
The development of stimuli-responsive small molecules for probing biologically active antioxidants such as glutathione (GSH) has important ramifications in the detection of oxidative stress. An ideal sensor for biological applications should exhibit sufficient sensitivity and selectivity for detection at physiological concentrations and be reversible to allow continuous and dynamic monitoring of antioxidant levels. Designing a suitable sensor thus requires a detailed understanding of activation properties and mechanism of action. In this work, we report a new set of GSH-responsive spiropyrans and demonstrate how changes in the electronic structure of spiropyrans influence GSH sensing with high specificity versus other structurally similar and biologically relevant redox-active molecules. The sensitivity, selectivity, kinetics, binding constant, and reversibility of GSH-responsive-substituted spiropyrans were investigated using UV-vis spectroscopy and laser irradiation experiments. Detailed studies of the mechanism of interaction between spiropyrans with GSH were investigated using NMR spectroscopy. Understanding how electronic effects impact the sensing ability of spiropyrans toward antioxidants and elucidating the mechanism of the spiropyran-GSH interaction will facilitate the design of more effective sensors for detection of antioxidants in vivo.